Entropy and Theodicy: A New Patristic Framework for Understanding Corruption - Torrance, Eugenia (Theology and science, 2020)
The second law of thermodynamics challenges theologians: they must affirm that the very same world that tends towards death and decay has been created by a God of love. R. J. Russell has drawn on two competing theodicies to respond to the second law: the arc of creation, fall, and redemption as found in Augustine and a paradigm of progress inspired by Irenaeus. While both systems explain the presence of corruption, both are ultimately unsatisfactory. This paper presents an alternative framework for a theodicy of natural evil inspired by John of Damascus.